Dying in cancer centers: Do the circumstances allow for a dignified death?. Issue 20 (8th September 2014) - Jors, Karin; Adami, Sandra; Xander, Carola; Meffert, Cornelia; Gaertner, Jan; Bardenheuer, Hubert; Buchheidt, Dieter; Mayer‐Steinacker, Regine; Viehrig, Marén; George, Wolfang; Becker, Gerhild
<x xml:space="preserve">Abstract</x> BACKGROUND Prior research has shown that hospitals are often ill‐prepared to provide care for dying patients. This study assessed whether the circumstances for dying on cancer center wards allow for a dignified death. METHODS In this cross‐sectional study, the authors surveyed physicians and nurses in 16 hospitals belonging to 10 cancer centers in Baden‐Wuerttemberg, Germany. A revised questionnaire from a previous study was used, addressing the following topics regarding end‐of‐life care: structural conditions (ie, rooms, staff), education/training, working environment, family/caregivers, medical treatment, communication with patients, and dignified death. RESULTS In total, 1131 surveys (response rate = 50%) were returned. Half of the participants indicated that they rarely have enough time to care for dying patients, and 55% found the rooms available for dying patients unsatisfactory. Only 19% of respondents felt that they had been well‐prepared to care for the dying (physicians = 6%). Palliative care staff reported much better conditions for the dying than staff from other wards (95% of palliative care staff indicated that patients die in dignity on their ward). Generally, physicians perceived the circumstances much more positively than nurses, especially regarding communication and life‐prolonging measures. Overall, 57% of respondents believed that patients could die with dignity on their ward. CONCLUSIONS Only about half of the respondents perceived that a dignified death is possible on their ward. We recommend that cancer centers invest more in staffing, adequate rooms for dying patients, training in end‐of‐life care, advance‐care planning standards, and the early integration of specialist palliative care services. Cancer 2014;120:3254–3260. © 2014 American Cancer Society.